Adjusting mean arterial pressure alarms improves the time spent within blood pressure targets in patients with septic shock: A quasi-experimental study. Issue 4 (July 2021) - Florens, Nans; Chabert, Beatrice; Stevic, Neven; Vareon, Julie; Malatray, Arnaud; Argaud, Laurent; Cour, Martin
Abstract: Background: Norepinephrine is the first-line vasoactive drug in septic shock. As underdosages or overdosages can be harmful for patients, it seems useful to maintain the mean arterial pressure (MAP) within preset bounds. Objectives: We sought to assess whether adjusted MAP alarms could improve MAP control in patients with septic shock. Methods: We conducted a quasi-experimental before-and-after study. During two consecutive periods, data on MAP control were obtained from patients with septic shock (n = 50/period) treated with norepinephrine over more than 24 h. The norepinephrine administration protocol, including prescription of the MAP target range (e.g., 65–75 mmHg), was identical during the two periods. During the first period (control group), the preset alarms of the monitor were used (i.e., low and high systolic blood pressure alarms set at 90 and 160 mmHg, respectively). During the second period, adjusted MAP alarms were implemented, with upper and lower bounds corresponding to the prescribed MAP target range (MAP-Alarm group). The primary end point was the percentage of time outside the desired MAP target range during the first 24 h of norepinephrine infusion. Results: Baseline characteristics were not significantly different. The primary end point was significantly lower in the MAP-Alarm group than in the control group (25 ± 13% versus 51 ± 18%, respectively; p < 0.01). MAP was higher than the target 14 ± 11% of the time in the MAP-Alarm group versus 37 ± 17% in the control group (p < 0.01) and lower than the target 11 ± 9% of the time in the MAP-Alarm versus 21 ± 22% in the control group (p < 0.05). There was no significant difference between the two groups with regard to the dose of norepinephrine, duration of norepinephrine administration, and survival. Conclusions: These results suggest that adjusting MAP alarms to the desired MAP target range could dramatically improve the percentage of time spent within MAP targets in patients with septic shock but does not reduce exposure to norepinephrine.